2019
DOI: 10.1111/clr.13529
|View full text |Cite
|
Sign up to set email alerts
|

A complete physical mapping of the vitamin D receptor gene for dental implant loss: A pilot study

Abstract: Objectives The aim of this pilot case–control study was to investigate the association of clinical variables and genetic polymorphisms in the vitamin D receptor gene (VDR) with dental implant loss. Material and Methods This study was carried out with 244 individuals with mean age 51.90 ± 11.28 (81 cases and 163 controls matched by age, sex, and smoking habit). Also, the clusterization phenomenon was investigated stratifying the sample into two groups: (a) 34 patients with multiple losses (presenting two or mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…The studies varied in design, ranging from case reports and case–control studies to a randomized trial. Specifically, two studies were case–control [ 21 , 26 ], three were case reports [ 22 , 23 , 24 ], one was a case series [ 24 ], one a retrospective cohort study [ 25 ], and one a randomized trial [ 27 ]. This assortment of study designs reflects the multifaceted approach researchers have taken to examine the relationship between Vitamin D and dental implant osseointegration.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The studies varied in design, ranging from case reports and case–control studies to a randomized trial. Specifically, two studies were case–control [ 21 , 26 ], three were case reports [ 22 , 23 , 24 ], one was a case series [ 24 ], one a retrospective cohort study [ 25 ], and one a randomized trial [ 27 ]. This assortment of study designs reflects the multifaceted approach researchers have taken to examine the relationship between Vitamin D and dental implant osseointegration.…”
Section: Resultsmentioning
confidence: 99%
“…In terms of quality of evidence, the review found a mix. Two studies [ 21 , 26 ] from Brazil and one from Italy [ 25 ] were rated as having a medium quality of evidence. In contrast, three studies [ 22 , 23 , 24 ]—from the USA, the United Kingdom, and Germany—were categorized as low in evidence quality.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The flowchart shown in Figure 1 illustrates each step in the search and screening process. The articles excluded and the reasons for their exclusion are shown in Table 1 [ 24 , 25 , 26 , 27 , 28 ]. In this review, the study by Mangano et al [ 29 ] was considered a continuation of the study by Mangano et al [ 30 ], so it was treated as a single study for purposes of data extraction.…”
Section: Resultsmentioning
confidence: 99%
“…Alvim-Pereira et al 24 failed to find any association between failure of osseointegration around implants and the genotypic variation of VDR gene which didn't agree with the present findings. In 2019, Pereira et al 25 suggested a possible role of allele G of rs3782905 of VDR in the recessive model may in dental implant loss in patients who lost two or more dental implants. The authors recommended further replication of their study to confirm their findings.…”
Section: Discussionmentioning
confidence: 99%